Principles of Microeconomics Scarcity and Social Provisioning - Dean, Erik; Elardo, Justin; Green, Mitch; Wilson, Benjamin; Berger, Sebastian (Open textbook library., 2016)
Principles of Microeconomics: Scarcity and Social Provisioning takes a pluralistic approach to the standard topics of an introductory microeconomics course. The text builds on the chiefly neoclassical material of the OpenStax Principles of Economics text, adding extensive content from heterodox economic thought. Emphasizing the importance of pluralism and critical thinking, the text presents the method and theory of neoclassical economics alongside critiques thereof and heterodox alternatives in both method and theory. This approach is taken from the outset of the text, where contrasting definitions of economics are discussed in the context of the various ways in which neoclassical and heterodox economists study the subject. The same approach–of theory and method, critique, and alternative theory theory and method–is taken in the study of consumption, production, and market exchange, as well as in the applied theory chapters. Historical and contemporary examples are given throughout, and both theory and application are presented with a balanced approach. This textbook will be of interest especially to instructors and students who wish to go beyond the traditional approach to the fundamentals of microeconomic theory, and explore the wider spectrum of economic thought. Instructors may contact Open Oregon Educational Resources for quiz question test banks associated with each chapter.